High-performance microfibrillated cellulose-based low voltage electroactive ionic artificial muscles in bioinspired applications. (1st January 2022) - Wang, Fan; Kong, Yang; Shen, Fangfang; Wang, Yaofeng; Wang, Donghai; Li, Qinchuan
Abstract: The development of electroactive high-performance biofriendly artificial muscles with large mechanical bending deformation, fast response time, low actuation voltage, and excellent durability is highly desirable for human friendly electronics such as soft robots, active biomedical devices, wearable devices, and flexible haptic displays. Herein, we report a novel ultralow voltage high-performance ionic artificial muscle based on microfibrillated cellulose (MFC), ionic liquid (IL) as a plasticizer, and conducting polymer poly(3, 4-ethylene dioxythiophene)-polystyrene sulfonate (PEDOT: PSS) as electrodes. The proposed MFC-IL biocomposite membrane was fabricated through doping of MFC with IL. The PEDOT:PSS layers were uniformly deposited on surfaces of the MFC-IL membrane by using the dip-coating method. The designed MFC-IL actuator demonstrated a large bending strain (0.31% under a sinusoidal input voltage of ±1.5 V at 0.1 Hz), low actuation voltage (<2 V), fast response time (<2.5 s), and excellent actuation durability (98% retention for 2 h), all of which were mainly due to its relatively large specific capacitance (115.2 mF cm −2 ) and tuned mechanical properties, resulting from the strong ionic interactions and crosslinking of MFC fibers with IL. More importantly, bioinspired applications including the grapple robot, bionic medical stent, and artificial soft robotic finger have been successfully realized. Therefore, the newly designed MFC-IL ionic soft actuator and its bioinspired robotic designs will provide a viable way for developing next-generation artificial muscles, soft robotics, active medical devices, and flexible displays.